Synthetic and spectroscopic investigations of electron spin relaxation - Moseley, Ian, author; Zadrozny, Joseph M., advisor; Finke, Rick, committee member; Prieto, Amy, committee member; Buchanan, Kristen, committee member (Colorado State University. Libraries, 2025)
Molecular magnets (also referred to as single molecule magnets (SMMs)), are organometallic complexes which can retain their magnetization in the absence of an applied field. The loss of this magnetization due to environmental interactions is referred to as magnetic relaxation. Due to the small energy gap between electronic spin orientations, maintaining this magnetization typically requires the molecules be held at temperatures approaching absolute zero. This requirement is both costly and impractical for most of the envisioned applications, and as such considerable research efforts have been made to increase the operating temperatures of molecular magnets. This dissertation presents a series of investigations into the magnetic relaxation behavior of molecular magnets incorporating first-row transition metals coupled to adjacent spin centers through electron-electron interactions. Presented herein is a series of investigations which demonstrate a novel method for extending magnetic relaxation in spin-abundant environments, the synthesis and characterization of a low-coordinate iron species as a potential precursor to extended solids, the magnetic properties of a pair of iron-based coordination polymers, and an investigation into the design of electron paramagnetic resonance (EPR) imaging probes using spin forbidden transitions. This research serves as a starting point for future investigations into the control of magnetic relaxation phenomena through synthetic control of electron-electron interactions.
Keywords: magnetism; spectroscopy; chemical synthesis; spin relaxation; single molecule magnets